Current trends in surface air temperature changes in the Barents and Kara Seas region - T.K. Karandasheva; B.V. Ivanov; V.I. Demin; A.D. Revina; I.A. Ilyushchenkova; A.R. Antsiferova (Российская Арктика)
The aim of the study is to assess observed trends in the surface air temperature (SAT) in the Barents and Kara Seas under conditions of current global warming. Regular meteorological observations from 31 Russian and Norwegian meteorological stations (MS) were used. Time trends in SAT series for calendar months and the year as a whole were assessed for all MS. Parameters of linear regression equations were calculated, and statistical significance of the identified linear trends was assessed. Linear trends in average annual SAT values are statistically significant at p<0.01 and positive for the entire study region. The warming rate in the study region increases from the southwest to the northeast. The highest warming rate (>2 °C/10 years) is observed in the northern areas of the Barents and Kara Seas, the lowest (<0.75 °C/10 years) – in the southwestern ice-free part of the Barents Sea. Linear trends of SAT for the year are generally determined by the tendencies observed in October-February. The warming rate field has a clearly defined "relief" with an increase in the direction from the southwest to the northeast during these months. The warming rate field is uniform in the warm season (May-August), the rates do not exceed 1 °C/10 years. The restructuring of the warming rate field from a clearly defined "relief" to a uniform field and back is observed in March-April and September.